Introduction and Application of the Neutrosophic Ideal in Gamma-Near-Ring - Florentin Smarandache; Amr Elrawy; Susan F. El-Deken (Neutrosophic Sets and Systems)
In this paper, we present the notion of neutrosophic ideals in gamma-near-rings. Subsequently, an examination of basic properties related to these ideals is conducted. We also provide characterizations of neutrosophic ideals. Furthermore, we establish a neutrosophic ideal by utilizing a collection of ideals. Finally, we introduce an application.